Continuous Environmental Changes May Enhance Topographic Memory Skills. Evidence From L’Aquila Earthquake-Exposed Survivors - Piccardi, Laura; Palmiero, Massimiliano; Bocchi, Alessia; Giannini, Anna Maria; Boccia, Maddalena; Baralla, Francesca; Cordellieri, Pierluigi; D’Amico, Simonetta (Frontiers in Human Neuroscience, 2018)
Exposure to environmental contextual changes, such as those occurring after an earthquake, requires individuals to learn novel routes around their environment, landmarks, and spatial layout. In this study, we aimed to uncover whether contextual changes that occurred after the 2009 L’Aquila earthquake affected topographic memory in exposed survivors. We hypothesized that individuals exposed to environmental changes – individuals living in L’Aquila before, during and after the earthquake (hereafter called exposed participants, EPs) – improved their topographic memory skills compared with non-exposed participants (NEPs) who moved to L’Aquila after the earthquake, as only EPs had to modify their previous cognitive map of L’Aquila. We also hypothesized that memory improvement was selective for the navigational space and did not generalize across other spatial and verbal domains. To test these hypotheses, we compared the topographic and spatial memory skills of 56 EPs without post-traumatic stress disorder symptoms to the skills of 47 NEPs using the Walking Corsi Test (WalCT; memory test in the navigational space) and the Corsi Block-Tapping Test (CBT; visuospatial memory test in the reaching space); EPs and NEPs were matched for gender, education and general navigational skills. A sub-group of participants also underwent the Rey-Auditory Verbal Learning Test (verbal memory test). The results showed that EPs, in contrast to NEPs, showed better performances on topographic learning assessed using the WalCT rather than spatial learning assessed by the CBT. This outcome suggests the possibility that EPs specifically improved topographic memory. This effect may be due to continuous exposure to environmental changes that have required individuals to learn novel paths within the city and integrate novel information, such as “new towns”, into their pre-existing mental representation of the city. Implications and limitations of the study are discussed.